Melatonin downregulates the increased hepatic alpha-fetoprotein expression and restores pancreatic beta cells in a streptozotocin-induced diabetic rat model: a clinical, biochemical, immunohistochemical, and descriptive histopathological study - Alsharif, Khalaf F.; Hamad, Asmaa A.; Alblihd, Mohamed A.; Ali, Fatma Abo Zakaib; Mohammed, Sherine Ahmed; Theyab, Abdulrahman; Al-Amer, Osama M.; Almuqati, Malik Saad; Almalki, Abdulraheem Ali; Albarakati, Alaa Jameel A.; Alzahrani, Khalid J.; Albrakati, Ashraf; et al. (Frontiers in Veterinary Science, 2023)
Diabetes mellitus represents one of the chronic metabolic disorders. Hepatopathy is one of the serious effects that can result from diabetes mellitus. Melatonin is a potent endogenous antioxidant, which can control insulin output. However, little information is available about the potential association of melatonin and hepatic alpha fetoprotein expression in diabetes. This research study was conducted to for this aim and to assess the influence of Melatonin on diabetes-related hepatic injuries and how β cells of the pancreas in diabetic rats respond to MT administration. Forty rats were assigned into four groups at random (ten animals each); Group I: served as a normal control group. Group II: Diabetes mellitus (DM) induced group, a single dose of freshly prepared streptozotocin (45 mg/kg body weight) was intraperitoneally injected. Group III: Rats received 10 mg/kg/day IP melatonin (MT) intraperitoneally, over a period of four weeks. Group IV: (DM+MT), following the induction of diabetes, rats received melatonin (the same as in MT Group III). Fasting blood sugar, HbA1C, and serum insulin levels were assessed at the end of the experimental period. Evaluations of serum liver function tests were made. The pancreas and liver were examined histopathologically and immunohistochemically for insulin and Alpha Fetoprotein (AFP) antibodies, respectively. MT significantly modulates the raised blood glucose, HbA-1c and insulin levels induced by diabetes and decreased ALT and AST. Melatonin attenuated the diabetic degenerative changes in pancreas and hepatic histological structure, increased β cell percentage area and decreased AFP expression in the liver tissue. Melatonin attenuated diabetes induced hepatic injury via restoring pancreatic β cells in addition to its antioxidant effect which decreased hepatocyte injury. Collectively, the present study concluded that potential benefits of melatonin in downregulation of the increased hepatic alpha feto-protein expression and restored the pancreatic beta cells in streptozotocin induced diabetic rat model, suggesting its promising functions in treatment of diabetes.